Interactions Between Emodin and Efflux Transporters on Rat Enterocyte by a Validated Ussing Chamber Technique - Huang, Juan; Guo, Lan; Tan, Ruixiang; Wei, Meijin; Zhang, Jing; Zhao, Ya; Gong, Lu; Huang, Zhihai; Qiu, Xiaohui (Frontiers in Pharmacology, 2018)
Emodin, a major active anthraquinone, frequently interacts with other drugs. As changes of efflux transporters on intestine is one of the essential reasons why the drugs interact with each other, a validated Ussing chamber technique was established to detect the interactions between emodin and efflux transporters, including P-glycoprotein (P-gp), multidrug resistant associated protein 2 (MRP2) and multidrug resistant associated protein 3 (MRP3). Digoxin, pravastatin and teniposide were selected as the test substrates of P-gp, MRP2 and MRP3. Verapamil, MK571 and benzbromarone were their special inhibitors. The results showed that verapamil, MK571 and benzbromarone could increase digoxin, pravastatin and teniposide absorption and decrease their Er values respectively. Verapamil (220 μM) could significantly increase emodin absorption at 9.25 μM. In the presence of MK571 (186 μM), the Papp values of emodin from M-S were significantly increased and the efflux ratio decreased. With the treatment of emodin (185 μM, 370 μM and 740 μM), digoxin absorption was significant decreased while teniposide increased. These results indicated that emodin might be the substrate of P-gp and MRP2. Besides, it might be a P-gp inducer and MRP3 inhibitor on enterocyte, which are reported for the first time. These results will be helpful to explain the drug-drug interaction mechanisms between emodin and other drugs and provide basic data for clinical combination therapy.